PENERAPAN PERMAINAN MEMBACA ESTAFET SEBAGAI UPAYA MENINGKATKATKAN KEMAMPUAN MEMBACA PADA PESERTA DIDIK KELAS 1 DI SDN BULUJARAN LOR 03 - Hasyim Muzadi; Didit Yulian Kasdrianto; Ribut Prastiwi Sriwijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Research at SDN Bulujaran Lor 03 addresses the low reading interest of grade 1 students who have difficulty memorizing words and understanding reading due to boring conventional teaching methods. The aim is to apply the PEMTA (Relay Reading Game) method to make learning to read more fun and interactive, thereby increasing students' interest and reading ability. The study employed a two-cycle Classroom Action Research (PTK) methodology, two meetings for 3 class hours each. This method is assisted by letter card media and focuses on increasing student participation and understanding. The results showed a significant improvement: 89.65% of students finished cycle I with an average score of 74.58, while 100% of students finished cycle II with an average score of 82.75, compared to pre-cycle which was only 82.75% scored with a mean value of 73.20. This method is successful in increasing students' interest, reading ability, self-confidence and cooperation in learning.